Matte separated behavior from slag during the cleaning process by using waste cooking oil as carbon neutral reductant - Wang L.-C.; Wei Y.-G.; Zhou S.-W.; Li B.; Wang H. (Journal of Mining and Metallurgy. Section B: Metallurgy)
As a waste resource, waste cooking oil (WCO) has not been widely used. Based on the characteristics of WCO cracking, this study proposed to replace fossil-based reductant with WCO for copper slag cleaning, to solve the problem of carbon neutralization in this process. Copper slag cleaning experiments were carried out in a lab-scale electric furnace. The matte separated behavior from slag and the distribution of matte in slag were studied. The results showed that the Fe3O4 content decreases from 12.9 to 3.5 wt.% by injecting 2.2 mL of WCO into 300 g copper slag at 1250°C. The distribution of copper content in slag is gradient along the vertical direction. In the reduction stage, the excessive Fe3O4 is reduced and the fluidity of slag is improved. When the precipitation time is above 60 minutes, the copper content in the middle and upper slag is reduced to 0.57 wt.%, which realizes the copper slag cleaning by using WCO.